2011
DOI: 10.1016/j.jacc.2010.08.648
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Failure Following Chronic Pressure Overload Is Associated With Reduction in Left Ventricular Mass

Abstract: RVF in patients with CTEPH is associated with reversible reduction in LV free wall mass. In a rat model of RVF, myocyte shrinkage due to atrophic remodeling contributed to reduction in LV free wall mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 41 publications
8
84
2
1
Order By: Relevance
“…Nevertheless, BPA significantly ameliorated RV dilatation (RVEDVI and RVESVI), RV systolic dysfunction (RVEF), RV hypertrophy (RVMI and VMI), and interventricular septal bowing (septal inversion ratio). Furthermore, there were strong correlations between changes in RV However, this study found that BPA did not significantly affect LV volumes and function, which is consistent with the findings on PEA of IINO et al [21] and KREITNER et al [16], but inconsistent with those of REESINK et al [28] and HARDZIYENKA et al [29]. Some pulmonary hypertension reports have demonstrated that LV systolic and diastolic dysfunction may occur secondary to RV dysfunction through ventricular interaction, ventricular interdependence, early diastolic ventricular septal bowing, and hypertrophy of the interventricular septum [28,30].…”
Section: Beneficial Effects Of Bpa On Haemodynamics and Clinical Statussupporting
confidence: 84%
“…Nevertheless, BPA significantly ameliorated RV dilatation (RVEDVI and RVESVI), RV systolic dysfunction (RVEF), RV hypertrophy (RVMI and VMI), and interventricular septal bowing (septal inversion ratio). Furthermore, there were strong correlations between changes in RV However, this study found that BPA did not significantly affect LV volumes and function, which is consistent with the findings on PEA of IINO et al [21] and KREITNER et al [16], but inconsistent with those of REESINK et al [28] and HARDZIYENKA et al [29]. Some pulmonary hypertension reports have demonstrated that LV systolic and diastolic dysfunction may occur secondary to RV dysfunction through ventricular interaction, ventricular interdependence, early diastolic ventricular septal bowing, and hypertrophy of the interventricular septum [28,30].…”
Section: Beneficial Effects Of Bpa On Haemodynamics and Clinical Statussupporting
confidence: 84%
“…Iino et al found no significant change in LV function at 6 months after PEA, 25 whereas Hardziyenka et al noted reverse LV remodeling (increased LVEDVI and LVSVI) at 8 months after PEA. 26 Reesink et al noted that LV function normalized owing to the restoration of pulmonary hemodynamics and RV function at least at 4 months after PEA. 6 Based on the results of these PEA studies, 4-6 months may be needed to induce LV remodeling and improve LV function with PEA or BPA.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Iino et al found no significant change in LV function after PEA, 25 whereas Hardziyenka et al noted reverse LV remodeling (increased LVEDVI and LVSVI) after the procedure. 26 Galiè et al noted that two mechanisms are involved in the increase in LV size after effective medical treatment in pulmonary arterial hypertension (PAH): (1) increase in RVSV; and (2) decompression of the LV due to decreased RVEDV. 28 In the present study, the extent of the improvement of RVSVI and RVEF were correlated to that of LVEDVI and the extent of the improvement of ISA was also correlated with that of LVEDVI and LVSVI.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…ECG evidence of LVH had well predictive characteristics. LVH is a feature of left heart disease, whereas in PAH, left ventricular atrophy can be present [29]. Left atrial dilation on MRI has high predictive value when comparing PAH and left heart failure [30].…”
Section: Figurementioning
confidence: 99%